Amphipathic metal-containing macromolecules with photothermal properties. Issue 24 (23rd May 2017) - He, Xumin; He, Xiehua; Li, Shenyan; Zhuo, Kaiyue; Qin, Weixiang; Dong, Shuyu; Chen, Jiangxi; Ren, Lei; Liu, Gang; Xia, Haiping
Abstract : Metal-containing macromolecules with extraordinary properties have attracted a great deal of interest owing to their potential application in the development of functional materials. Abstract : Metal-containing macromolecules with extraordinary properties have attracted a great deal of interest owing to their potential application in the development of functional materials. Here, we report the synthesis of novel amphipathic metal-containing macromolecules by the click reaction of methoxypolyethylene glycol azides with a unique metalla-aromatic complex containing a terminal alkynyl group. The resultant amphipathic macromolecules self-assembled into micellar nanoparticles with diameters of ca. 145 nm in water, which exhibited high stability, water-dispersibility, biocompatibility, and excellent photothermal behavior under 808 nm laser irradiation. Our study opens promising avenues for providing metal-containing macromolecules as photothermal materials.